Identification of high-affinity Monoamine oxidase B inhibitors for depression and Parkinson’s disease treatment: bioinformatic approach of drug repurposing - Shahwan, Moyad; Prasad, Pratibha; Yadav, Dharmendra Kumar; Altwaijry, Nojood; Khan, Mohd Shahnawaz; Shamsi, Anas (Frontiers in Pharmacology, 2024)
Depression and Parkinson's disease (PD) are devastating neurological disorders that require the development of novel therapeutic interventions. Drug repurposing target predefined pharmacological targets is a widely use approach in modern drug discovery. Monoamine oxidase B (MAO-B) is a critical protein implicated in these conditions. In this study, we undertook a systematic exploration of repurposed drugs as potential inhibitors of MAO-B. Exploring a library of 3648 commercially available drug molecules, we conducted virtual screening using a molecular docking approach to target the MAO-B binding pocket. Two promising drug molecules, Brexpiprazole and Trifluperidol, were identified based on their exceptional binding potential and drug profiling. Subsequently, all-atom molecular dynamics (MD) simulations were performed on the MAO-B-ligand complexes for a trajectory of 300 nanoseconds (ns). Simulation results demonstrated that the binding of Brexpiprazole and Trifluperidol induced only minor structural alterations in MAO-B and showed significant stabilization throughout the simulation trajectory. Overall, the finding suggests that Brexpiprazole and Trifluperidol exhibit strong potential as repurposed inhibitors of MAO-B that might be explored further in experimental investigations for the development of targeted therapies for depression and PD.